Analisis Kepuasan Mahasiswa terhadap Layanan Akademik STAIN Jember: Analysis of Student Satisfaction with Academic Services at STAIN Jember - Abdul Rahim (Fenomena, 2013)
The results of the research revealed that: 1) most of the students are satisfied with the academic services of STAIN Jember (45.92%). However, 33.67% of the students state their dissatisfaction, 2) there are significant simultaneous and partial influences of the variables reliability, responsiveness, empathy, assurance, and tangible on student satisfaction with STAIN Jember’s academic services, and 3) the variable that has the dominant influence is the reliability variable. Hasil penelitian mengungkapkan bahwa: 1) sebagian besar mahasiswa puas dengan layanan akademik STAIN Jember (45,92%). Namun, 33,67% mahasiswa menyatakan ketidakpuasan, 2) terdapat pengaruh signifikan secara simultan dan parsial dari variabel reliabilitas, responsivitas, empati, jaminan, dan bukti fisik terhadap kepuasan mahasiswa atas layanan akademik STAIN Jember, dan 3) variabel yang memberikan pengaruh dominan adalah variabel reliabilitas.